2017
DOI: 10.3390/ma10040336
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Bioavailability of Three-Dimensional Graphene Foam in Biological Tissues

Abstract: Graphene-based materials with a three-dimensional (3D) framework have been investigated for a variety of biomedical applications because of their 3D morphology, excellent physiochemical properties, volume stability, and their controllable degradation rate. Current knowledge on the toxicological implications and bioavailability of graphene foam (GF) has major uncertainties surrounding the fate and behavior of GF in exposed environments. Bioavailability, uptake, and partitioning could have potential effects on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…DNA damage, cell cycle arrest and oxidative stresses inside the cell are the main cytotoxicity responses to GO and rGO when they are exposed to different cell lines, which are likely due to the generation of reactive oxygen species, and deregulation of antioxidant genes [7]. The biocompatibility of graphene varies from their counterparts owing to their size, shape, lateral dimensions, high specific surface area and surface chemistry [8]. Most of the studies to date have focused mainly on the toxicity induced by pristine graphene and GO but the biocompatibility of rGO has not been fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…DNA damage, cell cycle arrest and oxidative stresses inside the cell are the main cytotoxicity responses to GO and rGO when they are exposed to different cell lines, which are likely due to the generation of reactive oxygen species, and deregulation of antioxidant genes [7]. The biocompatibility of graphene varies from their counterparts owing to their size, shape, lateral dimensions, high specific surface area and surface chemistry [8]. Most of the studies to date have focused mainly on the toxicity induced by pristine graphene and GO but the biocompatibility of rGO has not been fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene has the potential to adsorb aromatic amino acids by π-π stacking [21] . Recent in vivo and in vitro studies [12] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [22] , [23] have shown the role of ROS in mediating the toxicity of graphene. A schematic illustration of the potential ROS-mediated mechanisms manifested by graphene in the cell is shown in Fig.…”
Section: Toxic Potential Of Graphene Family Nanomaterialsmentioning
confidence: 99%
“…Three-dimensional graphene networks in the form of a foam, sponge or aerogel have recently been assembled from individual graphene sheets using chemical vapour deposition templated methods, which also preserve the unique properties of individual graphene sheets. [Panel (f) is adapted from [12] , with permission of MDPI Publishing Group, Copyright 2015]. …”
Section: Introductionmentioning
confidence: 99%
“…Same result was presented by Chen et al (6) after exposure in vivo of zebra fish to GO; this group reported hepatocytes with vacuoles and a loose arrangement, necrosis and the disintegration of cell boundaries, all of which became more severe with increasing GO concentration. Tabish et al (39) showed that exposure of common carp to graphene foam (7 days) 5, 10 and 15 mg/l caused degeneration of hepatocytes, pyknosis, karyolysis, and karyorrhexis in nuclei of hepatocytes, degeneration of the central vein in the liver. Abnormal accumulation of triglycerides and other neutral lipids may cause formation of vacuoles in hepatocytes and can be accompanied by pathological lesions such as necrosis (14).…”
Section: Graphene Expression Multiple Histological Changes (A) Seconmentioning
confidence: 99%